Wood plastic composite from Batai (Paraserianthes falcataria) / Nazirah Jamaluddin and Nur Syuhada Abd Latif - Jamaluddin, Nazirah; Abd Latif, Nur Syuhada (2011)
This project was carried out to study about the properties of wood plastic composite by using the Batai wood. Batai is the new species that has a potential to be commercialized as the raw material in wood based industry as it is a fast growing species and now this species is planted in the most country. Till now there are no reports to date on the use of batai for Wood Plastic Composite (WPC). In line with the need to further exploit the potential use of batai, this study was undertaken to investigate the feasibility of the species in WPC manufacturing. For this study, four specimen having 0%, 5%, 10% and 15% of sawdust from batai (Paraserianthes falcataria) were mixed with polypropylene (plastic) and additive name Maleated Anhydride Polypropylene (MAPP) which is coupling agent and the rest four samples were cooking without MAPP application. MAPP is act as the variables.